CONCEPT “ACQUAINTANCE” (ON THE MATERIAL OF UKRAINE, ENGLAND AND USA) - Tkachenko , Nataliіa (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The purpose of the article is to describe the concept “acquaintance” to improve the people’s understanding of semiotic means of meeting people in Ukraine, Great Britain and the USA spreading them to the social norms of communication and international collaboration. The research engages the comparative analysis of people’s verbal or nonverbal means of meeting people in Ukraine, Great Britain and the USA, lexical semantics, interpretation, conceptual analysis which reveal the cultural stereotypes of different nations. People contact due to their origin, likings, knowledge of conventions and social situations. Verbal and nonverbal semiotics in implied senses can orient, prevent, provoke or stimulate acquaintance. The fatic function (of meeting people comprises cognitive, emotional and social (conventional) information. Communication performs various functions in life disclosing the implied senses of symbols and sayings: security, warning, calling, agreeing or refusing, relaxing or straining, pleasing or displeasing, attracting or repulsing, etc. Verbal and nonverbal signals can stimulate or provoke acquaintance, they can be deceiving or misunderstood. Observing meeting traditions in Ukraine, GB and USA one can notice the similar requirements of good disposition in words and face, some difference in expressions and nonverbal signals. The concept “acquaintance” reflects the space, time and person reference. In meeting traditions in Ukraine, GB and USA the similar requirements of good attitude are observed as the principal cultural element at the core of the concept as well as difference in verbal and nonverbal reference.. Changes in the conceptual semantics can be determined as mutual penetration of the contact making traditions in communication.______________References:• (n.d.). A guide to communication in USA: Life in the USA > American culture > Communication in the USA. Retrieved from https://usahello.org/life-in-usa/culture/communication/• Brasier, J. (2024). 19 British Phrases You Need to Know Before You Visit UK. Insightful by Insight Vacation. Retrieved from https://www.insightvacations.com/blog/british-phrases-and-slang-words/• British Greetings: Common Colloquial Phrases in Communication in England. (n.d.). Retrieved from https://www.google.com/search?q=common+colloquial+phrases+in+communication+in+England• Bugayova, I. V. (2007). Prazdniki v Rossii: kontsept i kul’turema [Holidays in Russia: concept and cultural terms]. Innovatsii v issledovaniyakh russkogo yazyka, literatury i kul’tury, 68-73. Plovdiv.• Chim amerikanski zhinki prityaguyut do sebe poglyad [Why the American women attract the eyes]. (2025). Lifestyle. Retrieved from https://best-home-ideas.com/2025/02/chim-amerikanski-zhinki-prityaguyut-do-sebe-poglyad• How do I make friends with English people? (n.d.). Quora. Retrieved from https://www.quora.com/How-do-I-make-friends-with-English-people• Medvid’, N., & Tsinko, S. (2023). Terminisystema cuchasnyh lingvokulturologichnoh doslidzhen’ [Therminosystem of the modern studies in cultural linguistics]. Aktualni problemy humanitarnykh nauk, 36(2), 147-152. https://doi.org/10.24919/2308-4863/36-2-23• Nikonova, V. G. (2011). Hudozhnii concept: procedura rekonstruktsii ta modeluvannia (na materiali tragedii W. Shekspira) [The artistic concept: the procedure of reconstruction and modeling (on the material of the tragedies by W. Shakespeare)]. Visnyk KNLU. Seriia Phililogiia, 14(2), 113-123.• Osoblyvosti-spilkuvannya-po-ukrainskomu [The specifics of Ukrainian communication]. (n.d.). Retrieved from http://see-you.in.ua/ua/page/osoblivosti-spilkuvannya-po-ukrainskomu• Oxford Learners Dictionaries. (n.d.). Acquaintance. Retrieved from https://www.oxfordlearnersdictionaries.com/definition/english/acquaintance• Pease, A. (1988). Body Language: How to Read Others’ Thoughts by Their Gestures. Adobe Reader.• Pravilo pershyh piaty pobachen, schob ne rosacharuvati i ne rozachruvatisia [The rule of the first five meetings not to disappoint and be disappointed]. (2025). Lifestyle.• (n.d.). Terms of Intercultural Communication. Retrieved from https://terms-intercultural-communication.slovaronline.com/330• Terekhova, S. I. (2015). Functsionalni osoblyvosty representatsiy sistemi prostorovih, chasovih I osobovih coordinat: printsipiali zauvazhennia [The functional specifics of the representations of the system of space, time and person coordinates: the principle remarks]. Problemy semantiky, pragmatiky, rechnnia textu, 34, 65-76.• Tlumachniy slovnik ukrains’koi movy [The interpretative dictionary of the Ukrainian language]. (n.d.). Retrieved from https://slovnyk.ua/index.php?swrd• Tochilkin, T. G. (2007). Kontsept “Znakomstvo” kak element kartiny mira v russkoyazichnom i angloyazichnom lingvokulturologicheskom prostranstve [Concept “Acquaintance” as an element of the world picture in the Russian and English cultural linguistic space]. kand. philol. nauk.• Yak navchitisya roztashovuvati do sebe lyudej: fahivtsi rozkrili 3 “sekreti” [How to learn to dispose people: the specialists disclosed 3 “secrets”]. (n.d.). Retrieved from https://zhenskiy.kyiv.ua/lifestyle/yak-navchitisya-roztashovuvati-do-sebe-lyudej-fahivtsi-rozkrili-3-sekreti-2/• Znayomstvo: Velikiy tlumachny slovnik suchasnoi movy [Acquaintance: The Big Explanatory Dictionary of the Modern Language]. (n.d.). Retrieved from https://slovnyk.me/dict/vts/
Keywords: semiotics, verbal and nonverbal means, meeting people, social and national distinctions, comparative analysis